(untitled) (Journal of Comilla Medical College Teachers’ Association, 2026)
Background: Migraine ranks as one of the most incapacitating disorders. A variety of drugs are recommended for the preventive management of migraines. Objective: The objective of this study was to assess the comparative effectiveness of Propranolol, Topiramate and their combination in the prophylaxis of migraines within the Bangladeshi demographic. Methods: This randomized control trial with a 2×2 factorial design on 120 diagnosed cases of migraine, divided into four equal intervention groups to receive placebo, Propranolol, Topiramate and combination of Propranolol and Topiramate. The reduction of headache frequency, proportion of ≥50% headache reduction and headache severity were compared among the groups. Results: Groups received Propranolol, Topiramate and combination of these two showed significantly greater reduction in all three variables studied than placebo group (p-values <0.001 in all comparisons, 0.02 between placebo and Topiramate-treated groups in proportion of ≥50% reduction in headache frequency). Propranolol-treated and Topiramate-treated groups did not show any significant difference. A greater reduction in frequency was observed in the group treated with both Propranolol and Topiramate (p-value 0.03 and 0.02) and proportion of ≥50% reduction in frequency (p-value 0.03 and 0.01) than Propranolol and Topiramate-treated groups. Conclusion: Propranolol and Topiramate, whether administered separately or in conjunction, demonstrate efficacy in the prevention of migraines. The combination of Propranolol and Topiramate is superior to the individual agents in mitigating the reducing headache frequency. J Com Med Col Teachers’ Asso Jan 2026; 30(1): 40-45